(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2023)
The given article is devoted linguocultural features of advertisement in linguistics. The main attention is paid to specific characteristics of advertising in languages. Advertising can be seen as an external reflection of culture. Each country speaks to itself through hundreds of thirty-second commercials that offer a look at everyday things that surround a person through the prism of culture.